GAMBARAN INDEKS LARVA AEDES AEGYPTI DI BUFFER WILAYAH KERJA BANDARA SEPINGGAN BALIKPAPAN - Abdurrakhman, Abdurrakhman (UNUSA Press, 2019)
The House index and Container Index in the buffer area of the working area of Balikpapan Sepinggan Airport is still above 1%, so the potential for the spread of dengue disease. Mobilization of people, goods and transportation equipment will increasingly affect the transmission of disease in ports and airports, especially for vector-borne diseases. This study aims to analyze the risk factors associated with larvae density of Aedes aegypti and describe the larvae index in the buffer zone of the Sepinggan Balikpapan Airport This study was a descriptive study with a cross sectional design. The sample in this study was 121 houses with a proportionate stratified random sampling, the research location was in the buffer zone of Sepinggan Balikpapan Airport in November 2018. The variables studied were houses with positive larvae containers, breeding sites and PSN behavior and larvasidation. The data was analyzed using the chi square test. There was a relationship between houses with larvae positive Aedes aegypti, behavior of Mosquito Nest Eradication (PSN) and larvasidation with larvae density of Aedes aegypti but not for breeding sites (p =0.00and95%CI=0.64),and (p=0.00and95%CI=0.34).Thedescription of several Aedes aegypti larvae index, namely House Index (HI) = 57.02%, Container Index (CI) = 24.36%, Bruteau Index (BI) = 148.76, and Flick Free Numbers (ABJ) = 42.98 %. Houses with larvae of Aedes aegypti larvae and PSN and larvasidation behavior were associated with larvae density of Aedes aegypti. The index of HI, CI and BI larvae is of high value so there is a risk of DBD transmission